Unlocking Customer Loyalty in Mobile Banking Services: The Mediating Effect of Customer Satisfaction - Padam Bahadur Lama; Prem Bahadur Budhathoki; Lachana Shakya (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Digital integration of the banking sector amplifies seamless operation that streamlines remote banking services, boosting client satisfaction and enhancing loyalty. Descriptive and explanatory designs have been employed to investigate the factors affecting the loyalty of customers in adopting digital banking services. The primary sources of cross-sectional data were accumulated by disseminating a structured questionnaire to purposively sampled 355 mobile banking service users in Kathmandu, Nepal. The data analysis was accomplished by adopting SEM with SmartPLS version 4.1.1.4. The findings of the study depicted a positive and significant effect of service quality and service security on customer satisfaction. Similarly, a positive and significant influence of customer satisfaction was found on customer loyalty. Moreover, the partial mediation effect of customer satisfaction was found between the service quality, service security, and customer loyalty. These findings can be useful to endorse favorable policies and stabilize secure digital banking operations, fostering customer satisfaction.